Development of guidance and counseling module on self-regulation of students in social relations - Ita Karina Bancin; Mudjiran Mudjiran; Rusdinal Rusdinal (RedWhite Press, 2019)
Self regulation is one way to improve students understanding of good social relations. This research aimed to plan module and to describe the level of applicability the guidance and counseling module on student self-regulation in social relations. The method used was ADDIE model development. The subjects of the research were three experts and three counselors. The used and practicality the module used instruments in the form of questionnaire. This research employed the research product trial. The data of the research were analyzed by using the Coefficient Concordance test of Kendall’s W. The result of the research showed that the module on self-regulation of students in social relation was effective to be used by counselor. The practicality degree of the module on self-regulation of students in social relations was highly valued for use by students.